Limits on WIMP Dark Matter using Sapphire Cryogenic Detectors - Jochum J.; Angloher G.; Bucci C.; Cooper S.; Cozzini C.; Stefano P. Di.; Feilitzsch F. von; Frank T.; Hauff D.; Jagemann T.; Keeling R.; Kraus H.; et al. (2003, 2003)
Title screen